Motivation for studying medicine: assessing the similarities between UK and Ghanaian medical students - Benjamin Clayton (PAGEPress Publications, 2016)
Countries around the world experience challenges in ensuring equal distribution of health workers. For countries faced with this problem, there are many benefits to international co-operation. Before this can occur, however, there needs to be an understanding of the homogeneity of medical students between countries. This paper assesses the similarities in motivation to study medicine between medical students from the United Kingdom (UK) and Ghana. A survey previously performed on fourth-year Ghanaian students was reproduced with medical students in the UK. Students were asked to record their motivation for studying medicine, opinions on future career [general practice (GP) for UK students and a rural position for Ghanaian students] and basic demographics. The results were compared between the two cohorts using Fisher's exact test. Of medical students, 302 from Ghana and 78 from UK completed the survey. Of students, 63.5 and 75.0% were classified as intrinsically motivated in Ghana and the UK, respectively. Apart from parental education status, student demographics were broadly similar. Within the UK cohort, 30.1% of students considered it likely that they would work in GP in their future careers. Medical students are similarly motivated between the two countries. This suggests that greater co-operation may be possible when tackling difficulties in human resources for health. This is especially relevant for the UK, as the level of students predicting a career in GP in this study remains well below the national target.